Nonrecurring Items in Debt Contracts - Beatty, Anne; Cheng, Lin; Zach, Tzachi (Contemporary Accounting Research, 2019)
ABSTRACT Using a large sample of debt contracts, we study the determinants of excluding nonrecurring items from covenant calculations. We investigate this choice across firms, across items, and through time. We find that nonrecurring items are more likely to be excluded when the agency costs of debt are higher and less likely to be excluded when they predict borrowers' performance. Our evidence further suggests that the interplay between agency costs and nonrecurring items' predictive ability affects the decision to exclude these items from covenant computations. Finally, when examining the exclusion by different nonrecurring item types, we find confirmatory evidence that the probability of exclusion decreases with the predictive ability for borrowers' future performance of major nonrecurring item types. Overall, our research extends the literature on the determinants of contract design and improves understanding of the usefulness of accounting information in debt contracting.